2011
DOI: 10.1080/15562948.2011.616807
|View full text |Cite
|
Sign up to set email alerts
|

Transition to Homeownership Among Immigrant Groups and Natives in West Germany, 1984–2008

Abstract: The present paper analyzes transitions to homeownership among immigrant groups and natives in West Germany over a 24-year period from 1984 to 2008. Using data from the German Socioeconomic Panel (GSOEP), we find that everything else being equal, Turks, ex-Yugoslavians, Southern Europeans and Eastern Europeans do not display any differences in transitions into homeownership. Immigrants from wealthy western countries and native Germans possess similar and higher transitions into homeownership.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 45 publications
(90 reference statements)
1
19
0
Order By: Relevance
“…Age may be particularly relevant in countries like Germany with more regulated or restrictive lending practices where people have to muster more savings to put down larger deposits (Blaauboer, 2010). In some contexts, greater difficulties and possibly discrimination in access to mortgage finance may explain why ethnic minorities and migrants frequently have lower rates of homeownership than the native majority (Davidov & Weick, 2011).…”
Section: Family Dynamics and Life Course Careersmentioning
confidence: 99%
“…Age may be particularly relevant in countries like Germany with more regulated or restrictive lending practices where people have to muster more savings to put down larger deposits (Blaauboer, 2010). In some contexts, greater difficulties and possibly discrimination in access to mortgage finance may explain why ethnic minorities and migrants frequently have lower rates of homeownership than the native majority (Davidov & Weick, 2011).…”
Section: Family Dynamics and Life Course Careersmentioning
confidence: 99%
“…Søholt 2007;Søholt and Astrup 2009), in the homeownership sector there can be discriminatory practices among banks or institutions providing capital for the purchase of housing if ethnic minorities are seen as less solvent customers (e.g. Davidov and Weick 2011). Therefore, immigrants may face stricter credit constraints than natives, decreasing the homeownership rate especially among lower-income immigrants.…”
Section: What Influences Immigrants' Entry To Homeownership?mentioning
confidence: 99%
“…Existing research has mostly found that differences in the general socio-demographic determinants of homeownership are insufficient explanations for the gaps (Krivo 1995;Haan 2007;Kim and Boyd 2009;Bråmå and Andersson 2010;Painter and Yu 2010;Sinning 2010;Davidov and Weick 2011;Zorlu et al 2014;Kauppinen and Vilkama forthcoming). This suggests that the effects of these determinants differ between natives and immigrants.…”
Section: Introductionmentioning
confidence: 99%
“…Although the SOEP is not specifically designed to study integration, it includes a sufficient number of respondents with an immigration background and useful indicators related to the topic. Several studies have utilized data provided by the SOEP to study integration of immigrants in Germany (Davidov and Weick, 2011;Diehl and Blohm, 2008;Hochman, 2011;Reinecke, Schmidt and Weick, 2005). 7 This paper focuses on first generation immigrants identified by their self-reported country of birth.…”
Section: Datamentioning
confidence: 99%
“…Their arrival can be divided into six waves (Münz and Ulrich, 1997 from East Germany and the former communist bloc, arriving in Germany during the late 1980s and the early 1990s (Münz and Ulrich, 2003). 4 While the legal status of immigrants in the united Germany was revised and regulated by the end of the 1990s, their integration remains a central issue, both on the political and public agenda as well as in the social sciences (Davidov and Weick, 2011;Luther, 2013;Raijman, Semyonov and Schmidt, 2003;Schlüter, Schmidt and Wagner, 2008). In recent years, the topic has regained dominance in both the public and academic spheres, as it became clear that inequality between native Germans and immigrants of the first generation persists into the second immigrant generation (Biedinger, Becker and Rohling, 2008;Constant and Massey, 2005;Diehl and Koenig, 2009;Kalter and Granato, 2001;Kristen and Dollmann, 2010).…”
Section: Introductionmentioning
confidence: 99%